Enhanced grain refinement and mechanical properties of AZ91 alloy by a novel Al-5.1 V-2.3B refiner containing VB2 and VB particles - Fan, Wenxue; Bai, Yu; Zuo, Guoliang; Hao, Hai (Materials & design, 2023)
[Display omitted] •The growth mechanisms of VB2 and VB particles followed the principle of atomic adsorption and grew layer by layer.•The Al-5.1 V-2.3B grain refiner exhibited a remarkable grain refinement effect on both as-cast/as-extruded AZ91 alloys.•Mechanical properties of the as-cast/as-extruded AZ91 alloys were improved by adding Al-5.1V-2.3B grain refiner.•The enhancement of mechanical properties was resulted from grain refinement, weakened texture and dislocation strengthening.•There were well-defined crystallographic orientation relationships between VB, VB2 particles and α-Mg. Addition of specialized master alloys containing effective nucleation substrates has become the most common practice in the casting industries. In this study, a novel Al-5.1V-2.3B grain refiner containing VB2 and VB particles was designed. The growth mechanisms of VB2 and VB particles in grain refiner followed the principle of atomic adsorption and growing layer by layer based on the fundamental crystal growth theories. Grain refinement and mechanical properties of AZ91 alloy induced by the grain refiner and subsequent extrusion were investigated. The average grain size of the as-cast AZ91 alloy decreased from 217 μm to 78 μm with the optimal addition of 1 wt% Al-5.1V-2.3B grain refiner, and the UTS, YS and EL of the as-cast AZ91 alloy were improved by 27.6 %, 42.0 % and 43.0 %, respectively. Mechanical properties of the hot extruded samples were further enhanced due to the grain refinement, weakened texture and dislocation strengthening. The matching relationships between VB2, VB particles and α-Mg were characterized with the assistance of the high-resolution transmission electron microscope and edge-to-edge models. There were good matching relationships between VB, VB2 particles and α-Mg, as [001] / [1 2¯1 0] in (110) / (10 1¯0) and [0001] / [1 2¯1 0] in (10 1¯0) / (0002), which were the key for grain refinement.